2013
DOI: 10.1136/gutjnl-2013-304695
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that two distinct crypt cell types secrete chloride and potassium in human colon

Abstract: In human colon, Cl(-) secretion originates from the dominant population of colonocytes expressing apical CFTR, whereas K(+) secretion is derived from a smaller population of goblet cells expressing apical BK channels. These findings provide new insights into the pathophysiology of secretory diarrhoea and should be taken into account during the development of anti-diarrhoeal drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 56 publications
4
22
0
Order By: Relevance
“…Meprin-β, a metalloendopeptidase involved in the detachment and release of mucus from goblet cells, as well as in the modulation of mucus properties (57), was poorly expressed in HF-fed mice compared with SD-fed mice. Therefore, a combination of down-regulation of Meprin-β expression reducing the apical release of mucin vesicles and dysfunction of the CFTR/NKCC1 complex altering the balance of electrolytes in the luminal fluid (62), all associated with an impairment of the PPAR-γ pathway (59), are likely to account for the collapse of the mucus barrier (55,57). Moreover, when we treated the mice with rosiglitazone, the Meprin-β staining was stronger in HF-rosi mice compared with HF-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…Meprin-β, a metalloendopeptidase involved in the detachment and release of mucus from goblet cells, as well as in the modulation of mucus properties (57), was poorly expressed in HF-fed mice compared with SD-fed mice. Therefore, a combination of down-regulation of Meprin-β expression reducing the apical release of mucin vesicles and dysfunction of the CFTR/NKCC1 complex altering the balance of electrolytes in the luminal fluid (62), all associated with an impairment of the PPAR-γ pathway (59), are likely to account for the collapse of the mucus barrier (55,57). Moreover, when we treated the mice with rosiglitazone, the Meprin-β staining was stronger in HF-rosi mice compared with HF-fed mice.…”
Section: Discussionmentioning
confidence: 99%
“…In human colonic mucosa, apical BK channels are also responsible for K ϩ secretion [which is induced by cAMP (117)] but are located exclusively in goblet cells (88). An earlier study had reported an expression only in surface cells and cells in the upper 20% of the crypt axis and had found that they are mainly composed of ␤ 1 and ␤ 3 subunits (116).…”
Section: K ϩ Channelsmentioning
confidence: 99%
“…They are the dominant basolateral K ϩ channels in human colonocytes (but not in goblet cells) and are expressed throughout the length of crypt axis (2,88). In fact, they are required for the cAMP-stimulated Cl Ϫ secretion through CFTR (cystic fibrosis transmembrane conductance regulator), which is independent of BK channel activation (117).…”
Section: K ϩ Channelsmentioning
confidence: 99%
“…BK channels | LRRC26 | secretory epithelium | salivary glands | SLO1 L arge-conductance, voltage-and Ca 2+ -regulated BK-type channels are widely expressed proteins, found not only in excitable cells, such as neurons, muscle, and endocrine cells, but also nonexcitable cells, including salivary (1) and lacrimal gland (2) acinar cells, and colonic crypt cells (3). Given the almost ubiquitous expression of BK channels among cells that play quite distinct physiological roles, it is particularly important to define the specific properties of BK channels in a given cell type and determine what the specific physiological role played by BK channels in a given cell may be.…”
mentioning
confidence: 99%